Autism Learning Mobile Application - SATIAKUMAR, MOHISHAA; MOHD YUSOF, MUNIRAH (Applied Information Technology And Computer Science, 2024)
The Autism Learning Mobile Application is designed for students aged 4 to 12 with autism. Developed using an agile methodology and an object-oriented approach, it aims to minimize risk through iterative improvements, allowing regular upgrades and continuous enhancements. Built with Flutter on Visual Studio Code and utilizing a NoSQL database, the app aims to improve daily skills, social skills, and overall quality of life for autistic children. Personalized materials tailored to each student's needs enhance its effectiveness, helping students develop language skills and improve social interactions. Key features include training videos, assessments, and a game hub, facilitating convenience, supervision, and collaboration between teachers and parents. This provides educational content and learning opportunities, especially for those unable to attend traditional school or needing extra support. The app reduces stress and anxiety by offering a safe environment where children can learn at their own pace, boosting self-esteem and confidence. Overall, the Autism Learning Mobile Application significantly enhances the quality of life for autistic children, helping them learn, grow, and develop in ways that may not be possible otherwise.